Transdermal absorption enhancement through rat skin of gallidermin loaded in niosomes - Aranya Manosroi (2018)
Gallidermin (Gdm) loaded in anionic niosomes composed of Tween 61/CHL/DP (1:1:0.05 molar ratio) gave the highest entrapment efficiency (45.06%). This formulation gave antibacterial activity against Propionibacterium acnes and Staphylococcus aureus with the MIC and MBC of 3.75 and 7.5; 7.5 and 15μg/μl, respectively. Gdm loaded in niosomes was more chemically stable than Gdm in aqueous solution of about 1.5 times. Gdm loaded and unloaded in niosomes were not found in the receiver solution investigated by vertical Franz diffusion cells at 37°C for 6h. Gdm loaded in niosomes showed higher cumulative amounts in viable epidermis and dermis (VED) of rat skin of about 2 times more than unloaded Gdm. Gdm loaded in niosomes and incorporated in gel exhibited the highest cumulative amounts (82.42±9.28μgcm-2) and fluxes (13.74±1.55μgcm-2h-1) in stratum corneum (SC) and comparative cumulative amounts (183.16±30.32μgcm-2) and fluxes (25.74±5.05μgcm-2h-1) in VED to the unloaded Gdm incorporated in gel. This study has suggested that Gdm loaded in anionic niosomes and incorporated in gel is the superior topical antibacterial formulation because of the high accumulation in the skin with no risk of systemic effect. © 2010 Elsevier B.V.